Protein misfolding in Dictyostelium: Using a freak of nature to gain insight into a universal problem - Malinovska, Liliana (Prion, 2015)
Prion-like proteins can undergo conformational rearrangements from an intrinsically disordered to a highly ordered amyloid state. This ability to change conformation is encoded in distinctive domains, termed prion domains (PrDs). Previous work suggests that PrDs change conformation to affect protein function and create phenotypic diversity. More recent work shows that PrDs can also undergo many weak interactions when disordered, allowing them to organize the intracellular space into dynamic compartments. However, mutations within PrDs and altered aggregation properties have also been linked to age-related diseases in humans. Thus, the physiological role of prion-like proteins, the mechanisms regulating their conformational promiscuity and the links to disease are still unclear. Here, we summarize recent work with prion-like proteins in Dictyostelium discoideum. This work was motivated by the finding that D. discoideum has the highest content of prion-like proteins of all organisms investigated to date. Surprisingly, we find that endogenous and exogenous prion-like proteins remain soluble in D. discoideum and do not misfold and aggregate. We provide evidence that this is due to specific adaptations in the protein quality control machinery, which may allow D. discoideum to tolerate its highly aggregation-prone proteome. We predict that D. discoideum will be an important model to study the function of prion-like proteins and their mechanistic links to disease.